1995
DOI: 10.1136/gut.36.6.853
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy for malignant tumours of the ampulla of Vater.

Abstract: (Gut 1995; 36: 853-856)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 17 publications
0
16
1
Order By: Relevance
“…In a pilot clinical trail, Bown et al [10] used PDT in the palliative treatment of 16 patients with cancers in the pancreatic head that could not be treated with surgery because of the advanced nature of the disease or the general condition of the patients, and they concluded that PDT may be of value for treating localized cancers in patients who are poor candidates for definitive surgery or in whom the location of tumor makes pancreatic resection inappropriate. Abulafi et al [29] and Tseng et al [30] reported that patients with pancreatic and ampullary carcinoma Xie Q et al . Gemcitabine and photodynamic therapy for pancreatic cancer who are not suitable for surgery should be treated with PDT, since PDT is both feasible and safe for small tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In a pilot clinical trail, Bown et al [10] used PDT in the palliative treatment of 16 patients with cancers in the pancreatic head that could not be treated with surgery because of the advanced nature of the disease or the general condition of the patients, and they concluded that PDT may be of value for treating localized cancers in patients who are poor candidates for definitive surgery or in whom the location of tumor makes pancreatic resection inappropriate. Abulafi et al [29] and Tseng et al [30] reported that patients with pancreatic and ampullary carcinoma Xie Q et al . Gemcitabine and photodynamic therapy for pancreatic cancer who are not suitable for surgery should be treated with PDT, since PDT is both feasible and safe for small tumors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the choice and timing of treatment remain a clinical challenge. A combined approach of endoscopic surveillance, with either endoscopic or surgical intervention, as necessitated by the type of lesion, has been shown to be successful during long term follow up of patients with FAP [10]. However, both endoscopic and surgical resection [11] of polyps have been plagued with recurrence of these lesions requiring continued surveillance.…”
Section: Introductionmentioning
confidence: 98%
“…The human duodenum is much thicker than that in the hamster and is likely to be much more resistant to perforation. Two preliminary clinical reports using PDT with Photofrin to treat duodenal and ampullary tumours showed an encouraging response with no perforations (Abulafi et al, 1995;Mlkvy et al, 1995). This suggests that it is likely to be safe to treat lesions in the human pancreas.…”
Section: Discussionmentioning
confidence: 93%